Irrigation Channel Automatic Control System - Rakhmatov Doniyor Khudayorovich; Makhkamov Bakhrom Azimzhonovich; Olimbaev Otajon Azamat ugli; Rakhmatova Durdonakhon Khudayor qizi (Zien Journals, 2021)
This paper discusses the creation of an automated process control system (APCS), which allows you to monitor the land reclamation condition and high-quality water supply for agricultural and domestic needs, with minimal operating costs. This system helps to improve the performance of irrigation and water supply canals, increase their productivity and reliability
Keywords: APCS; irrigation and water supply canals; water supply facility; APCS architecture